Microscopic detection and characterization of microplastics along Rivermouths in Borongan city, Eastern Samar, Philippines - Nibalvos, Aljon Victor G.; Nibalvos, Cristina T.; Acorin, Lylah Daisy A. (Edelweiss Applied Science and Technology, 2025)
The purpose of this study was to ascertain whether microplastics were present in the waters near rivermouths in the Eastern Samar, Philippines, area around Borongan City. Two filtration system meshes were used to filter 20 to 30 liters of sample per area: a 30 micron nylon mesh to separate the microplastics from the filtrate and a filter sieve to remove suspended particles. A 40x magnification stereomicroscope was used to view the residue. The water samples include microplastics, according to the results. Furthermore, the majority of the microplastics that were seen were primary microplastics, which are filamentous in size and shape and primarily microfibers. Subsequent investigation showed that blue and transparent/white were the most prevalent colors. There were 104 microplastics in all, or an average of 0.74 microplastics per liter of water sample. This study suggests the use of microplastics as indicator of aquatic environmental contamination or pollution, as well as degradation.